The Transformation of Regional Government Policies in Maintaining Economic and Health Stability in the New Normal Era - Yulia Rimapradesi; Siti Fajrina (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2021)
It has been more than one year that the Covid-19 pandemic has hit Indonesia. In the face of this pandemic, governments from the national and district levels have responded with policies that limit social activities, resulting in decreased mobility in the community to prevent the transmission of Covid-19. This ultimately has an impact on economic growth. In addition, policies in the health sector are also the main thing, starting from the handling of Covid19 patients at the beginning of the pandemic to the provision of vaccines in the New Normal era. The focus of this writing will look at the transformation of local government policies in the New Normal era of two districts in Indonesia, namely South Bengkulu (Bengkulu) and Pidie (Aceh) to maintain economic stability and health in their regions. By using a policy implementation approach and qualitative descriptive analysis methods, this article aims to understand how local government policies transform in the pandemic era. This study concludes that the policy transformation of the local government of Bengkulu Selatan and Pidie districts in maintaining economic stability and the district generally follows the rules from the central government, but is adjusted to the situation and conditions of the district, such as the Covid-19 transmission rate and the budget owned by each region respectively.